Chemical Castration in Indonesia: Limiting an Absolute Human Right - Louisa Elsie Heathcote (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
In 2016, the Indonesian government enacted Government Regulation in Lieu of Law Number 1 of the year 2016, adapted into Law number 17 of the year 2016. This regulation introduces chemical castration as a criminal sanction for child sex offenders, spurring human rights concerns. This article aims to assess whether chemical castration constitutes cruel, inhuman, or degrading treatment from the perspective of Article 7 of the International Covenant on Civil and Political Rights and whether such a human rights violation can be justified. This article employs the normative research method, studying principles of law, systems of law, the synchronization of the law, the history of the law and policies, and laws in comparison to one another. The article bases its findings on laws, books, journals, judgments, and other documents.This article finds that firstly, chemical castration constitutes cruel, degrading, or inhuman treatment and secondly, that such a violation can be justified according to the limitations of human rights. The significance of this article is the basis for the increased limitation of human rights to advance the cause of child protection.